The Evaluation of clarification process of Indonesia’s sweet sorghum juice by ultrafiltration membrane and the physicochemical and sensorial properties of the sugar product - CAHYADI, Wisnu; GHAFFAR, Rizal Maulana; DARNIADI, Sandi; SARIFUDIN, Achmat; SAGITA, Diang; BUDIHARTI, Uning; Hari Hariadi; NURHASANAH, Ana; WIDODO, Puji; HARIADI, Hari; HARYANTO, Aidil; ANDRIANTO, Moeso; et al. (Food Science and Technology, 2024)
The juice derived from Sorghum bicolor L. exhibits a notable sugar content, rendering it a promising candidate for use as a sweetening agent. The presence of impurities in sorghum juice encompasses several substances such as non-sugar molecules, non-fermentable reducing agents, starch, and minerals like salt, magnesium, and calcium. The objective of this study was to investigate the impact of ultrafiltration (UF) membranes on the physicochemical properties of sorghum juice and sugar granules, as well as to identify customer preferences for these products. The study consisted of three primary phases. The first phase involved investigating the impact of 0–3 cycles of UF treatment on the physicochemical properties of the sorghum juice. The second stage involved comparing the characteristics of sugar granules obtained through UF and non-ultrafiltration (non-UF) methods. The third one focused on examining the preference of sorghum sugar granules in their natural state and as a sweetener for steeped black tea. A 5% significance level was employed in this work to conduct multivariate methodology of variance and the Friedman nonparametric test. The findings of the study indicate that the use of UF treatment has a simultaneous impact on the turbidity and color of sorghum juice. Non-UF sorghum sugar granules exhibit a superior aroma in comparison to UF granules while maintaining identical color, taste, and texture. Consumers exhibited a preference for steeped black tea sweetened with palm sugar, followed by rock sugar, granulated sugar, UF sorghum sugar granules, and non-UF.